Affective Assesment Instrument to Assess Student Attitudes Towards Science, Technology, Engineering and Mathematics - Rahmayani, Fadillah; Istiyono, Edi (Journal of Education Reseach and Evaluation, 2022)
The assessment instrument is part of the learning toolkit which includes the process of measuring and collecting data and information to be processed and interpreted in it to consider how decisions on student learning outcomes are achieved in accordance with learning objectives. Instruments are used to measure cognitive, psychomotor, and affective dimensions. So far there has not been much research on the development of an affective instrument, mostly focusing on students' cognitive and psychomotor aspects. Thus, this study aims to develop affective instruments, namely students' attitudes towards STEM (Science, Technology, Engineering and Mathematics). This research is research and development using the ADDIE development model. The ADDIE model consists of five steps: analysis, design, development, implementation, and evaluation. The initial instrument that was developed was 45 items which contained every STEM aspect which was then tested on test subjects totaling 72 high school students. Based on the results of data analysis, a good and effective attitude assessment instrument has been produced to assess students' attitudes to see students' attitudes towards STEM. Through this development, it is hoped that it can become a foundation that can be used by educators before giving appropriate treatment to students in preparing students who have an attitude towards STEM aspects so that students can face various challenges of the 21st century which are so tight and growing rapidly.